The Role of National Values in the Family in Child Education - O.A.Sharipova (Research Parks Publishing LLC, 2021)
The article discusses the role of the family and national values in the upbringing of children. Thoughts on the example of parents in the upbringing of children, the positive impact of a healthy lifestyle in the family are also shown. The importance of national values in the upbringing of children is also highlighted in detail. Every parent in an Uzbek family should feel from the heart that a child needs to develop humanism, love for the Motherland, faith, responsibility, devotion to our sacred traditions, passion for science, cultural skills. Therefore, the main school of child rearing is the relationship between a couple and a parent. Raising a child is one of the most important issues for parents.